Evaluation of the Impact of Internal Audit, Good Corporate Governance, and Intellectual capital on Financial Perfomance - Fauziyah, Nurul; Rochmatullah, Mahameru Rosy (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
Financial performance serves as a key signal of a firm’s stability and operational effectiveness. This research investigates how Internal Audit, Good Corporate Governance (GCG), and Intellectual Capital (IC) shape banks’ financial outcomes, assessed through Non-Performing Loans (NPL), Return on Assets (ROA), and Return on Equity (ROE). A quantitative design was applied, utilizing secondary data extracted from the annual reports of 44 banks listed on the Indonesia Stock Exchange during 2019–2023. Multiple linear regression, processed via SPSS, was employed for analysis. Results reveal that Internal Audit and Intellectual Capital exert a significant positive effect on financial performance, whereas GCG shows no notable influence. Collectively, the three variables demonstrate a significant role in determining banking performance. The study underscores the necessity of reinforcing internal audit practices and optimizing intellectual resources to safeguard financial resilience, while also advancing theoretical discourse in banking risk management.